2019
DOI: 10.1111/myc.12915
|View full text |Cite
|
Sign up to set email alerts
|

Overview and outcome of mucormycosis among children with cancer: Report from the Children's Cancer Hospital Egypt

Abstract: Summary Mucormycosis represents a real challenge in immunocompromised patients. This study aimed to describe the clinical characteristics, treatment outcome and infection‐related mortality in our patients at the Children's Cancer Hospital 57357, Cairo, Egypt. This is a retrospective study during the period 2007‐2017. Data analysis included demographic data, risk factors, diagnostic workup, treatment and outcome. During the study period, 45 patients developed proven mucormycosis according to EORTC/MSG criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 22 publications
9
37
1
Order By: Relevance
“…In Egypt, a 10-year study in a pediatric oncology center, reported 45 cases of proven invasive fungal sinusitis which is comparable to the relative incidence present in other countries. 20,21 In our institution, nearly 5 to 7 invasive fungal sinusitis cases are diagnosed per year. Unusually, a notably rising number of this infection has been recorded recently in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, a 10-year study in a pediatric oncology center, reported 45 cases of proven invasive fungal sinusitis which is comparable to the relative incidence present in other countries. 20,21 In our institution, nearly 5 to 7 invasive fungal sinusitis cases are diagnosed per year. Unusually, a notably rising number of this infection has been recorded recently in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting retrospective study conducted along a decade from 2007 to 2017 in children’s cancer hospital 57,357 in Egypt, only 45 patients reported mucormycosis [ 55 ]. Zaki et al in 2010 reported 10 cases within 12-month duration analysis of admitted cases to Ain Shams specialized hospital with only 2 cases had a sinus mucormycosis and 8 cases had pulmonary mucormycosis [ 56 ], while in the current case series, 100% of the cases had a sinus infection.…”
Section: Discussionmentioning
confidence: 99%
“…In North Africa, proven mucormycosis developed in 45 patients in which 90% of the cases had hematological malignancies in Egypt; in addition to mucormycosis-related complications in 5 cases with disfigurement and perforated hard palate. Mucormycosis-related mortality was 33% [124]. In December 2010, 3 out of 5 acute leukemia patients due to Rhizomucor outbreak [125].…”
Section: Mucormycosismentioning
confidence: 99%